Adoption of improved forage grasses in Western Kenya - Oulu, Martin (Bioversity International and the International Center for Tropical Agriculture, 2020)
This working paper presents the results of a study commissioned by the International Centre for Tropical Agriculture (CIAT) under the Grass2Cash project whose primary objective was to understand the underlying reasons why farmers adopt ten improved forage varieties in the four Western Kenya counties of Kakamega, Bungoma, Busia and Siaya. A gendered perspective to the motivations and challenges of adoption, and a review of the project assumptions were secondary objectives. A total of 61 adoptee farmers were purposively sampled from a CIAT database of farmers given the improved forages, 19 non-adoptees selected through snowball sampling, and 10 stakeholders (CIAT/SAC staff, government officers, and peer farmers) were interviewed face to face and through telephone between June and August 2020